Xeno-free bioengineered human skeletal muscle tissue using human platelet lysate-based hydrogels - Fernández-Garibay, X. (2022)
Bioengineered human skeletal muscle tissues have emerged in the last years as newÂ in vitroÂ systems for disease modeling. These bioartificial muscles are classically fabricated by encapsulating human myogenic precursor cells in a hydrogel scaffold that resembles the extracellular matrix. However, most of these hydrogels are derived from xenogenic sources, and the culture media is supplemented with animal serum, which could interfere in drug testing assays. On the contrary, xeno-free biomaterials and culture conditions in tissue engineering offer increased relevance for developing human disease models. In this work, we used human platelet lysate (PL)-based nanocomposite hydrogels (HUgel) as scaffolds for human skeletal muscle tissue engineering. These hydrogels consist of human PL reinforced with aldehyde-cellulose nanocrystals (a-CNC) that allow tunable mechanical, structural, and biochemical properties for the 3D culture of stem cells. Here, we developed hydrogel casting platforms to encapsulate human muscle satellite stem cells in HUgel. The a-CNC content was modulated to enhance matrix remodeling, uniaxial tension, and self-organization of the cells, resulting in the formation of highly aligned, long myotubes expressing sarcomeric proteins. Moreover, the bioengineered human muscles were subjected to electrical stimulation, and the exerted contractile forces were measured in a non-invasive manner. Overall, our results demonstrated that the bioengineered human skeletal muscles could be built in xeno-free cell culture platforms to assess tissue functionality, which is promising for drug development applications.